1972
DOI: 10.2307/1238711
|View full text |Cite
|
Sign up to set email alerts
|

Separable Programming for Considering Risk in Farm Planning

Abstract: This paper proposes use of separable programming for selecting farm enterprises which are efficient in terms of expected income and income variance. An empirical application on a croplivestock farm in the Columbia Basin of Washington is presented. The effects of removing statistically insignificant covariance terms and the error introduced by the linear approximation are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Hazell and Scandizzo [21] and Paris [33] are some examples of a large number of studies which developed several variants of risk programming models. Several empirical investigations have also been made using these models in selecting optimal crop mix and in testing the behaviourial assumptions of the producers towards risk [10,16,18,24,25,28,32,37]. Binswanger [8,9] using an experimental gambling approach to study the attitude towards risk of semi-arid tropical farmers of India concluded that wealth does not influence risk significantly at higher pay-off levels and that differences in investment behaviour could not be explained by the differences in their constraint sets.…”
Section: The Modelmentioning
confidence: 99%
“…Hazell and Scandizzo [21] and Paris [33] are some examples of a large number of studies which developed several variants of risk programming models. Several empirical investigations have also been made using these models in selecting optimal crop mix and in testing the behaviourial assumptions of the producers towards risk [10,16,18,24,25,28,32,37]. Binswanger [8,9] using an experimental gambling approach to study the attitude towards risk of semi-arid tropical farmers of India concluded that wealth does not influence risk significantly at higher pay-off levels and that differences in investment behaviour could not be explained by the differences in their constraint sets.…”
Section: The Modelmentioning
confidence: 99%
“…No attempt was made in the article by Thomas, et al, [2 ] to solve the example problem by QP. However, this point is not discussed here.…”
Section: Comparing Et¡ Frontiersmentioning
confidence: 99%
“…However, this point is not discussed here. The decision maker is usually concerned with the resulting farm enterprise combinations and with the actual solution E, V relationshŸ Therefore the "efficiency frontier" shown in Figure 2 of [2] is meaningless and obviously wrong in the sense that no curve on that diagram is positioned to show its comparative efficiency. The total income variance restraint, specified asa right-hand side value for equation (2.1), is measured in the vertical axis.…”
Section: Comparing Et¡ Frontiersmentioning
confidence: 99%
“…Thomas et al have used separable programming to approximate the nonlinear total variance constraint when the mean return is maximized [4,10].…”
mentioning
confidence: 99%